Propuesta de evaluación neuropsicológica para casos donde exista una alteración en la percepción musical (2015)
There are different conditions which are not considered as relevant because they are not totally disabling. Yet when a patient regards a symptom or a specific condition as important, it should be taken seriously, because it may be an essential part of that person. Music is considered as one of the biggest reinforcers for humans, as well as a great tool for neuropsychological stimulation. But little has been investigated in relation to this issue. It is recommended to integrate the musical area as part of the neuropsychological evaluation and intervention. This article aims to build a proposed neuropsychological assessment for cases where there is an alteration in the perception of music. Through a single case study, and from a standard neuropsychological assessment protocol, along with specific additional evidence about music, it ends with a proposal that includes differential diagnoses such as depression, musical anhedonia and amusia. As a contribution states that it is a proposal that, in addition to novelty, it should be taken into account due to the relevance that involves the musical component; and the fact that assess the patient holistically, not only on their overall cognitive state but also emotional and always taking into account what the patient needs.